An Efficient On-Line Algorithm for Edge-Ranking of Trees - Rahman, Muntasir Raihan (2008)
An edge-ranking of a graph G is a labeling of the edges of G with positive integers such that every path between two edges with the same label ° contains an edge with label ¸ > °. In the on-line edge-ranking model the edges e1; e2 : : : ; em arrive one at a time in any order, where m is the number of edges in the graph. Only the partial information in the induced subgraph G[fe1; e2; ... ; eig] is available when the algorithm must choose a rank for ei. In this paper, we present an on-line algorithm for ranking the edges of a tree in time O(n2), where n is the number of vertices in the tree.